Edukasi anemia pada remaja dan tata laksana pemberian tablet tambah darah - Deddy Utomo; Tinah Purwaningsih; Ta'adi Ta'adi; Fatchurrozak Himawan (JOURNAL of Public Health Concerns, 2026)
Background: Anemia remains a major health issue among adolescents in Indonesia, particularly among adolescent girls. Anemia can lead to reduced learning concentration, productivity, and immune function, while also posing risks to future reproductive health. Health education and the provision of iron-folic acid (IFA) tablets are crucial strategies for preventing and managing anemia among adolescents. Purpose: To improve adolescent knowledge regarding anemia and the administration of iron-folic acid tablets through health education activities. Method: This community service activity was conducted in Debongkulon Urban Village on Monday, June 15, 2026, with 20 adolescents participating as respondents. The activity focused on empowering adolescents through education and health screening. The procedure prioritized interactive dialogue and active group participation to enhance health literacy regarding anemia prevention. All field observation data were compiled descriptively to provide a comprehensive evaluation of the program's implementation. Results: The majority of respondents had hemoglobin (Hb) levels within the normal range (75.0%) and Body Mass Index (BMI) values ​​in the normal category (50.0%); regarding knowledge, the majority demonstrated a good level of understanding (70.0%). Improvements in knowledge covered the definition of anemia, recognition of signs and symptoms, associated risks and negative impacts, and understanding of prevention strategies. Conclusion: Health education regarding anemia and iron (Fe) supplementation protocols effectively increased adolescents' knowledge and can serve as a promotive-preventive strategy to prevent anemia in this age group. Suggestion: Schools are encouraged to conduct periodic anemia education, while parental support and regular monitoring by health workers are needed to ensure consistent consumption of iron supplements (TTD) among adolescents. Keywords: Adolescents; Anemia; Iron supplements; Treatment management Pendahuluan: Anemia masih menjadi salah satu masalah kesehatan utama pada remaja di Indonesia, terutama remaja putri. Anemia dapat menyebabkan penurunan konsentrasi belajar, produktivitas, daya tahan tubuh, serta berisiko memengaruhi kesehatan reproduksi di masa mendatang. Edukasi kesehatan dan pemberian tablet tambah darah (TTD) merupakan strategi penting dalam pencegahan dan penanggulangan anemia pada remaja. Tujuan: Meningkatkan pengetahuan remaja mengenai anemia serta tata laksana pemberian tablet tambah darah melalui kegiatan edukasi kesehatan. Metode: Kegiatan pengabdian ini dilaksanakan di Kelurahan Debongkulon pada hari Senin tanggal 15 Juni 2026 dengan sebanyak 20 remaja sebagai responden. Sasaran kegiatan adalah menitikberatkan pada pemberdayaan remaja melalui edukasi dan skrining kesehatan. Prosedur kegiatan mengedepankan dialog interaktif dan partisipasi aktif kelompok untuk meningkatkan literasi kesehatan terkait pencegahan anemia. Seluruh data hasil observasi lapangan disusun secara deskriptif sebagai bentuk evaluasi komprehensif atas pelaksanaan program. Hasil: Menunjukkan sebagian besar responden memiliki kadar Hb dalam kategori normal (75.0%), indek masa tubuh responden sebagian besar berada pada kategori normal (50.0%) dan untuk aspek pengetahuan, mayoritas responden memiliki tingkat pengetahuan dalam kategori baik (70.0%). Mendapatkan peningkatan pengetahuan meliputi pengertian tentang anemia, memahami tanda dan gejala kejadian anemia, risiko dan dampak negatif dari anemia serta pemahaman tentang upaya pencegahan terjadinya anemia. Simpulan: Edukasi kesehatan mengenai anemia dan tata laksana pemberian Fe efektif meningkatkan pengetahuan remaja dan dapat menjadi salah satu strategi promotif-preventif dalam upaya pencegahan anemia pada kelompok usia remaja. Saran: Diharapkan pihak sekolah perlu melaksanakan edukasi anemia secara berkala dan dukungan dari orang tua serta petugas kesehatan perlu melakukan monitoring rutin terhadap konsumsi TTD pada remaja secara teratur.